2020
DOI: 10.1186/s12872-020-01433-0
|View full text |Cite
|
Sign up to set email alerts
|

Patency of conduits in patients who received internal mammary artery, radial artery and saphenous vein grafts

Abstract: Background Where each patient has all three conduits of internal mammary artery (IMA), saphenous vein graft (SVG) and radial artery (RA), most confounders affecting comparison between conduits can be mitigated. Additionally, since SVG progressively fails over time, restricting patient angiography to the late period only can mitigate against early SVG patency that may have occluded in the late period. Methods Research protocol driven conventional angiography was performed for patients with at least one of each… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The use of the IMA graft has been an essential advance in myocardial surgical revascularization. Long-term patency rates of this and other arterial conduits are higher than those with saphenous vein grafts, especially when used for the LAD [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the IMA graft has been an essential advance in myocardial surgical revascularization. Long-term patency rates of this and other arterial conduits are higher than those with saphenous vein grafts, especially when used for the LAD [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al in 1995 [ 3 ] reported two patients, 61 and 71 years old, who had atherosclerosis of both the left and right IMAs at the time of surgical revascularization. The IMAs were heavily calcified in both patients and were not suitable for grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Patent grafts isolation is essential for a successful redo CABG 10 , as it can contravene the protective effects of cardioplegia by maintaining a continuous flow of normal warm blood with low pottasiun. Moreover, in redo coronary surgery where previous venous graft is present, intraoperative myocardial infarction may occur due to thrombus dislodgment during manipulation of venous grafts 11 .…”
Section: Case Reportmentioning
confidence: 99%
“…Injury to an ITA graft has been associated with a mortality rate of 17.9% 14 . Another risk associated with resternotomy where previous grafts are present is intraoperative myocardial infarction because of thrombus dislodgment during manipulation of venous grafts, which carry a higher risk of thrombosis compared with arterial grafts 15 . If the patent ITA and the venous graft have adhered to the back of the sternum, an anterolateral thoracotomy may be helpful to dissect the heart in patients who need revascularization 16 .…”
Section: Introductionmentioning
confidence: 99%